PENGARUH BAURAN PROMOSI, HARGA DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN MAHASISWA MEMILIH STMIK WIDURI JAKARTA - Agus Indra P; Nora Andira Brabo; Moh Shidqon (EBID: Ekonomi Bisnis Digital, 2024)
Price and Service Quality on Students' Decision to Choose STMIK Widuri Jakarta. The research methodology used in this study is quantitative. The data used are primary data obtained from distributing questionnaires with a Likert scale (1-5). The population in this study were students who had studied at STMIK Widuri, Jakarta, with a sample of 204 people. Data analysis for hypothesis testing used multiple linear regression with the help of SPSS software version 26. The results showed that Promotion Mix and Service Quality had a significant positive effect on the decision to study at STMIK Widuri Jakarta. While Price had a significant negative effect on the decision to study at STMIK Widuri Jakarta. Managerial contributions to increasing student interest in choosing STMIK Widuri Jakarta are:The New Student Admissions Department (PMB) is friendlier, more polite in promoting STMIK, and improving the content of promotional advertising messages.  Adjusting tuition fees as the quality of facilities increases. Improving the quality of service, quality of lecturers, employees, facilities and infrastructure, and libraries.